Afrikaner identity after Nationalism: young Afrikaners and the "new" South Africa - Blaser, Thomas Michael (My University, 2009)
ABSTRACT Towards the end of the twentieth century, Afrikaner nationalism has significantly declined – how can we explain that such a strong and dominant ethno-nationalist movement has become powerless? From a theoretical perspective, I argue that we have to analyze the formation and dissolution of identities. Modernist approaches to the study of Afrikaner nationalism and ethnicity focus on the state in shaping identities that were supportive of nationalist mobilization. While the state certainly matters, I want to suggest that we have to integrate these historical and political accounts closer with subjectivity. Subjective aspects of nationalism are best reflected in narratives of the self. These narratives are analyzed in four categories: reflecting on the apartheid past; living in an African society; language and culture; and relating to “black” South Africans. In narrating the self, young Afrikaners give us insights into processes of ethnic and nationalist mobilization. These narratives indicate that living in a consumer society in late modernity has contributed to the formation of identities that are multiple, contradictory and contingent and hence are not readily available for ethno-nationalist mobilization.